2006
DOI: 10.1016/j.jmps.2006.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-dynamics simulation-based cohesive zone representation of intergranular fracture processes in aluminum

Abstract: A traction-displacement relationship that may be embedded into a cohesive zone model for microscale problems of intergranular fracture is extracted from atomistic molecular-dynamics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
129
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 201 publications
(134 citation statements)
references
References 52 publications
1
129
0
Order By: Relevance
“…The GB thus formed is a <1 1 0> ∑99 symmetric tilt GB. Crack propagation along this GB has been extensively studied by MD simulations [36][37][38] at a cryogenic temperature of T = 100 K.…”
Section: Example Of An Edge Crack Simulation Along a Grain Boundary Imentioning
confidence: 99%
See 2 more Smart Citations
“…The GB thus formed is a <1 1 0> ∑99 symmetric tilt GB. Crack propagation along this GB has been extensively studied by MD simulations [36][37][38] at a cryogenic temperature of T = 100 K.…”
Section: Example Of An Edge Crack Simulation Along a Grain Boundary Imentioning
confidence: 99%
“…In the stresses discussed in [36][37][38], it was found that, while in one direction the crack becomes blunted by deformation twinning, in the opposite direction it propagates in a brittle-like manner with very little dislocation emission. The latter direction has been chosen as the propagation direction for the edge crack of the simulation in Figure 12.…”
Section: Example Of An Edge Crack Simulation Along a Grain Boundary Imentioning
confidence: 99%
See 1 more Smart Citation
“…For fracture simulations, the traction-displacement relationship (as introduced by Dugdale and Barenblatt [3,4]), is used to model the cohesive properties of the grain boundary (GB) interface for a specific fracture mode. The traction-displacement relationship in this strategy is extracted from atomistic molecular dynamics (MD) simulations [5], and is incorporated into cohesive-zone models (CZM) [6] used in finite element models [7]. This yields a finite element analysis capability to study the behavior of metallic microstructural damage at the grain scale [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a methodology for extracting CZMs from atomistic simulations of crack propagation has been developed [5]. In this paper, the concept of implementing a statistical CZVE ensemble to extract a CZM constitutive law in terms of a traction-displacement relationship will be used in an improved coupled atomistic-continuum model for intergranular fracture in aluminum.…”
Section: Introductionmentioning
confidence: 99%